Hard and wear resistant VB2 coatings deposited by pulsed DC magnetron sputtering. (January 2017) - Ge, Fangfang; Chen, Chunli; Shu, Rui; Meng, Fanping; Li, Peng; Huang, Feng
Abstract: Vanadium boride (VB2 ) coatings have been less concerned, although they have advantages of super-hardness as well as self-lubrication. In this study, VB2 coatings were deposited by pulsed DC magnetron sputtering, and the effect of deposition parameters on the microstructure, mechanical and tribological properties of coatings were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nano- and micro-indentation, and ball-on-disk tribometer. Under the growth condition with high adatom mobility, the coatings exhibited complete (001) orientation and dense texture. A nanocomposite structure that nanocolumns were separated by a secondary phase was especially observed in the coating deposited at 773 K. Both hardness and intrinsic stress of the coatings were improved substantially by increasing the substrate bias or the pulse frequency. The coating deposited at −30 V and 250 kHz, had the hardness of ∼43.6 GPa and the compressive stress of ∼2.0 GPa. Under the load of 2 N, the friction coefficients were ∼0.7 against Al2 O3 counterpart, and the wear rates were in the range of 7 × 10 −16 –8 × 10 −16 m 3 /N m. Under the load of 5 N, the coatings with low intrinsic stress showed better wear resistance, with the wear rate of 10 −16 m 3 /N m. Highlights: VB2 coatings were deposited using pulsed DC magnetron sputtering. Effect of the deposition parameters on the structure and properties was studied. The dense VB2 coatings have high hardness (>30 GPa). The VB2 coatings exhibits good wear resistance with the wear rate of 10 −16 m 3 /N m.